2010
DOI: 10.1038/onc.2009.507
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 is required for oncolytic NDV replication in human cancer cells and establishes a link between tumorigenesis and sensitivity to oncolytic virus

Abstract: Oncolytic Newcastle disease virus (NDV) replicates selectively in most human tumor cells but not in normal cells. The relationship between tumorigenesis and the selective susceptibility of most tumor cells to oncolytic NDV replication is poorly understood. A multistage skin carcinogenesis model derived from non-tumorigenic HaCaT cells was used to systematically investigate the molecular mechanisms involved in the oncolytic NDVsensitivity associated with tumorigenic transformation. No significant differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 41 publications
2
56
0
Order By: Relevance
“…NDV replication has been linked to defects in the antiviral response of cancer cells. However, in our previous studies and other recent studies, many cancer cell lines have been shown to have a functional and intact IFN response after NDV infection (20,28,45,49). To detect IFN induction in A549-neo and A549-Bcl-xL cells and to demonstrate that the IFN produced inhibits NDV replication, we performed the IFN induction bioassay (Fig.…”
Section: Expression Of Influenza Virus Ns1 Protein By Ndv Delays Apopmentioning
confidence: 99%
“…NDV replication has been linked to defects in the antiviral response of cancer cells. However, in our previous studies and other recent studies, many cancer cell lines have been shown to have a functional and intact IFN response after NDV infection (20,28,45,49). To detect IFN induction in A549-neo and A549-Bcl-xL cells and to demonstrate that the IFN produced inhibits NDV replication, we performed the IFN induction bioassay (Fig.…”
Section: Expression Of Influenza Virus Ns1 Protein By Ndv Delays Apopmentioning
confidence: 99%
“…Interestingly, for the oncolytic Newcastle disease virus (NDV), Rac1 expression was reported to be sufficient to render non-tumorigenic cells susceptible to NDV replication which identified Rac1 as a potential oncogene. 234 …”
Section: Transformationmentioning
confidence: 99%
“…NDV also encounters a range of antiviral responses, which are proposed to depend on the protein kinase R (PKR)-induced PKR/eIF2a signalling cascade and sequestosome 1 (SQSTM1)-mediated selective degradation of mitochondria by autophagy, called 'mitophagy' (Meng et al, 2014;Zhang et al, 2014). Meanwhile, there is increasing evidence suggesting that other classes of genes, such as the interferon-inducible protein ISG12a and IFNgamma-signalling mediator Rac1, are also involved in virus-host interactions (Liu et al, 2014;Puhlmann et al, 2010). In addition to hosts, viruses, such as herpes simplex virus 1 (HSV-1) (Mostafa et al, 2013), human cytomegalovirus (HCMV) (Cantrell & Bresnahan, 2005), influenza virus (IV) (Goodman et al, 2011) and others (Saribas et al, 2014;Stracker et al, 2004;Trobaugh et al, 2014), regulate host and viral genes to enhance viral replication.…”
mentioning
confidence: 99%